Impacts of Crop Sequence and Tillage Management on Soil Carbon Stocks in South‐Central North Dakota. Issue 4 (7th July 2016) - Halvorson, Jonathan J.; Liebig, Mark A.; Archer, David W.; West, Mark S.; Tanaka, Donald L.
Abstract : Core Ideas: After 18 years of a study, we measured soil properties and estimated soil C. Estimates based on equivalent mass (SOCem ) exceeded those based on fixed depth. Stocks of SOCem were not affected by cropping sequence at any partition depth. We found more SOCem for no‐till than minimum tillage at cumulative depths ≥30.5 cm. Organic C in the 0–7.6‐cm depth had increased, in 2012, by about 16% since 2001. Emphasis is placed on developing robust, productive, economically competitive, and environmentally benign agroecosystems. In 2012, after 18 yr of a study to evaluate the effects of crop sequence and tillage, we measured soil properties at various depths to 91.4 cm and estimated soil C. The experiment, near Mandan, ND, was a split‐plot design, with crop sequence as whole plots and tillage (minimum tillage or no‐till) as subplots. Crop sequences included continuous spring wheat ( Triticum aestivum L.) with crop residue retained or removed, spring wheat–millet [ Setaria italica (L.) Beauv.], spring wheat–safflower ( Carthamus tinctorius L.)–fallow, spring wheat–safflower–rye ( Secale cereale L.), and spring wheat–fallow. Soil organic C, calculated by the equivalent mass method (SOCem ), was consistently higher ( P < 0.001) than when calculated by the fixed‐depth method. Disparities between the two methods, greatest near the soil surface, were attributable to tillage. Estimates of SOCem were not affected by cropping sequence at any depth, averaging about 26, 47, 73, 114, and 156 Mg ha −1 in the 0‐ to 7.6‐, 0‐ to 15.2‐, 0‐ to 30.5‐, 0‐ to 61.0‐, and 0‐ to 91.4‐cm partitions. Tillage had no influence at depths <30.5 cm, but no‐till plots contained more SOCem than minimum tillage plots in the 0‐ to 61‐cm (115 vs. 112 Mg ha −1 ) and 0‐ to 91.4‐cm (158 vs. 153 2.3 Mg ha −1 ) partitions ( P < 0.05). Soil organic C in the 0‐ to 7.6‐cm depth increased by an average of 3.2 Mg ha −1 or 16% since 2001. This study suggests that C sequestration in soil is less impacted by the choice of crop sequence than by tillage.